2019
DOI: 10.3389/fnins.2019.00490
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Childhood Experiences and Telomere Length a Look Into the Heterogeneity of Findings—A Narrative Review

Abstract: Background: Adverse childhood experiences (ACEs) have been associated with poor mental and somatic health. Accumulating evidence indicates that accelerated biological aging—indexed by altered telomere-related markers—may contribute to associations between ACEs and negative long-term health outcomes. Telomeres are repeated, non-coding deoxyribonucleic acid (DNA) sequences at the end of chromosomes. Telomeres shorten during repeated cell divisions over time and are being used as a marker of biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 104 publications
(315 reference statements)
2
37
4
Order By: Relevance
“…However, there was no evidence that current psychological distress impacted telomere length. Recent studies and metaanalyses have continued to demonstrate the relationship between childhood adversity and telomere shortening (Tyrka et al, 2016;Ridout et al, 2018;Bürgin et al, 2019). Furthermore, this relationship between childhood adversity and telomere length existed among individuals with anxiety disorders and controls.…”
Section: Telomere Shorteningmentioning
confidence: 98%
“…However, there was no evidence that current psychological distress impacted telomere length. Recent studies and metaanalyses have continued to demonstrate the relationship between childhood adversity and telomere shortening (Tyrka et al, 2016;Ridout et al, 2018;Bürgin et al, 2019). Furthermore, this relationship between childhood adversity and telomere length existed among individuals with anxiety disorders and controls.…”
Section: Telomere Shorteningmentioning
confidence: 98%
“…Attachment security might be an important moderator between stressors and health outcomes, as was shown between childhood adversity and cellular aging ( 89 ). Considering attachment security in future research might account for some of the heterogeneity found in the association between (early) stressors and cellular aging across studies ( 4 , 90 ). Thus, more research in particular on attachment security in high stress environments and high-risk samples is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual abuse was more strongly and consistently associated with telomere length than physical abuse. Two recent meta-analyses and one narrative review also concluded that the type of adverse experiences have different impacts on telomere length, though they did not demonstrate differences between sexual and physical abuse [ 27 , 56 , 57 ]. Li et al (2017) found that experiences of childhood separation were associated with shorter telomeres, but physical and sexual abuse and loss of a parent were not [ 56 ], while in Ridout et al (2018), experiences of abuse and neglect were associated with shorter telomeres [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings of greater impact of abuse earlier in life may reflect a true impact of abuse experienced in a key developmental period [ 59 , 60 ], or longer duration of abuse exposure. Abuse duration is not captured well by current measures [ 57 ]. We attempted to address this by cross-classifying abuse in childhood and adolescence, which showed, that among individuals that experienced physical or sexual abuse in childhood, around half were also abused in adolescence.…”
Section: Discussionmentioning
confidence: 99%